Pengaruh Sosial Media Pada Perkembangan E-Commerce di Lingkungan Mahasiswa - Yoga Bagus Pratama (International Journal Administration, Business & Organization, 2022)
The purpose of this study was to determine the influence of social media on the development of e-commerce in the student environment. This research uses descriptive survey research. The population for this study were students. The data collection technique used a questionnaire with a total of 113 respondents. The analytical method used is simple linear regression analysis which aims to find the effect of variable x (social media) with variable y (e-commerce). The results of the analysis from each table are that variable x (social media) has an influence on variable y (e-commerce) by 35.8%.